Optimalisasi Peran Kepala Sekolah dalam Manajemen Hubungan Sekolah dan Masyarakat di SMK Darur Roja Cinere Depok: Optimizing the Role of the School Principal in School–Community Relationship Management at SMK Darur Roja Cinere Depok - Suhaedi, Ukat (UNIB Press, 2025)
The relationship between schools and communities plays a strategic role in supporting educational quality and institutional sustainability. The principal holds a central managerial position in optimizing this relationship through leadership, communication, and participatory governance. This study aims to analyze the role of the principal in managing school-community relations at SMK Darur Roja Cinere Depok. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and documentation. The findings reveal that the principal plays a crucial role as a communicator, mediator, and decision-maker in strengthening cooperation with parents and the surrounding community. However, several challenges were identified, including limited community participation, communication gaps, and the absence of structured management mechanisms. The study concludes that optimizing the principal’s role requires strategic leadership, transparent communication, and systematic engagement with stakeholders. These findings contribute to the development of effective school-community management practices in vocational education institutions.